World Economic Outlook, April 2006 : Globalization and Inflation. (World Economic Outlook; World Economic Outlook ;, 2007)
The World Economic Outlook is the product of a unique international exercise in information gathering and analysis performed by IMF staff to guide key initiatives and to serve IMF member countries. Published at least twice a year in English, French, Spanish, and Arabic, the World Economic Outlook offers a comprehensive picture of the international economic situation and prospects for the future. With its analyses backed by the expertise and resources of over 1,100 IMF economists, the World Economic Outlook is the authoritative reference in its field. Today, even small economic fluctuations can trigger major financial swings. It's vital to have the latest perspective on what's happening and where it could lead in the coming months and years. The World Economic Outlook brings you that perspective, giving you analyses, forecasts, and figures you'll use all year long.